PERAN AKUNTANSI TERHADAP PENGAMBILAN KEPUTUSAN BISNIS MELALUI ANALISIS BIG DATA (STUDI LITERATUR) - Oon Feriyanto; Agnia Nurul Ilmi; Vani Aulia; Luvita Hesti Jandriani; Shely Safitri; Eneng Irmayanti (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Big Data is a term for a very large and complex set of data that cannot be processed using traditional means. This data comes from various sources such as social media, sensors, and business transactions. Through proper data analysis, Big Data can provide important insights in helping companies understand consumer behavior, improve operational efficiency, and make better decisions. However, managing Big Data requires sophisticated technology and also requires special attention to data privacy and security. In making data-based decisions, it is of course important for companies to have a good data management strategy, including high data quality, smooth data integration and reliable analytics. Thus, Big Data is not only a tool for understanding the past and current conditions, but Big Data is also an important part of planning the future and making more informative, accurate and effective business decisions.